Neptune's laboratory fantasy, fear, and science at sea - Adler, Antony (Harvard University Press, 2019)
Neptune's Laboratory traces shifts over the last two centuries in the imagination of ocean space by scientists, policy makers, and the public. Oceans gained prominence in the public's imagination in the early nineteenth century as scientists first probed the depths, and marine fisheries were industrialized. It wasn't long, however, before some fishermen, policy makers, and scientists grew concerned that fish stocks could be exhausted. In Europe, these fears gave rise to new internationalist aspirations as scientists sought to conduct research on an ocean-wide scale and nations struggled to protect their fisheries. The internationalist program for marine research was disrupted by the start of World War I. Nevertheless, we find a resurgence of internationalist dreams in evocations of a Pacific World at world fairs on the west coast of the United States, both during the interwar period and as late as the 1960s. With the arrival of the Cold War, ocean spaces were re-cast as both battlefields, post-apocalyptic living spaces, and as utopian frontiers by scientific visionaries, policy makers, and the public. Late into the twentieth century, dreams of a new global political internationalism, with ocean spaces and marine science as its foundation, persisted.--Provided by publisher.